Local Fabrication and installation of Improved Fish Drying Racks to Promote Women’s Participation - Kilanga, Lucyphine; Kakwasha, Keagan; Kitogo, Lawrence; Simbila, Deogratius; Muzungaire, Lizzy; Lukanga, Editrudith; Mudege, Netsayi (WorldFish, 2024)
This detailed activity report outlines the comprehensive approach taken to construct drying racks. This technology can promote women’s fish processors’ participation in the fisheries value chain and their economic resilience to the economic impacts of climate change in the sector. The technology was selected based on a study on women’s fisherfolk’s resilience